2018
DOI: 10.1155/2018/2051687
|View full text |Cite
|
Sign up to set email alerts
|

Seismic Energy Assessment of Buildings with Tuned Vibration Absorbers

Abstract: Seismic analysis and energy assessment of building installed with distributed tuned vibration absorbers (d-TVAs) are presented. The performance of d-TVAs is compared with single tuned vibration absorber (STVA) installed at the top of the building. The placements of the d-TVAs are based on the modal properties of the uncontrolled and controlled buildings. The governing equations of motion of the building with the STVA and d-TVAs are solved by employing Newmark’s integration method. Various energies under earthq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 38 publications
(35 reference statements)
1
23
0
Order By: Relevance
“…Later, Elias et al showed the application of the d‐MTMDs in mitigation of the wind and earthquake responses of a tall reinforced concrete chimney. Elias et al, Gill et al, and Elias reported that the performance of the d‐MTMDs is significant in seismic response reduction of the benchmark building, and they showed robust dynamic response reduction achieved thereby. The detailed literature survey on passive TMDs is provided by Elias and Matsagar …”
Section: Introductionmentioning
confidence: 99%
“…Later, Elias et al showed the application of the d‐MTMDs in mitigation of the wind and earthquake responses of a tall reinforced concrete chimney. Elias et al, Gill et al, and Elias reported that the performance of the d‐MTMDs is significant in seismic response reduction of the benchmark building, and they showed robust dynamic response reduction achieved thereby. The detailed literature survey on passive TMDs is provided by Elias and Matsagar …”
Section: Introductionmentioning
confidence: 99%
“…Using equation (1) and the time scale of approximately 1 : 133, the pressure coefficients measured over 27 sec were converted into an hour-long wind force data. ese wind force data (alongwind and across-wind directions) can be altered to signify larger or smaller wind velocities by multiplying the given time histories by (U/V i ) 2 , where U is the desired mean wind velocity at the i th story of the benchmark structure. As recommended by Yang et al [35], for the performance evaluation of the control systems, only the first 15 mins in 900 s of across-wind data is enough for the computation of building response.…”
Section: Numerical Studymentioning
confidence: 99%
“…Optimally designed TMDs (tuning frequency optimized) have been found to be more effective than conventional ones, where the TMDs are tuned exactly to the frequency of the main structure. Multiple TMDs (MTMDs) are more effective when they are distributed along the height of the structure (d-MTMDs); their optimal placement depends on modal properties of the uncontrolled and controlled structures [2][3][4][5][6][7][8][9]. Advanced TMD schemes such as particle TMDs and TMDs with inerter are more effective than the optimal TMDs [10][11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Lu et al [2] reported that the particle TVAs are more effective than the optimal TVAs. The researchers presented the multi-mode response control of tall structure by different TVA schemes [3][4][5][6][7][8][9][10]. They concluded that the distribution of the multiple TVAs (d-MTVAs) as per modal properties of the structures caused maximum responses reduction.…”
Section: Introductionmentioning
confidence: 99%